Downwind pre‐aligned rotors for extreme‐scale wind turbines. Issue 7 (8th March 2017) - Loth, Eric; Steele, Adam; Qin, Chao; Ichter, Brian; Selig, Michael S.; Moriarty, Patrick
Abstract: Downwind force angles are small for current turbines systems (1–5 MW) such that they may be readily accommodated by conventional upwind configurations. However, analysis indicates that extreme‐scale systems (10–20 MW) will have larger angles that may benefit from downwind‐aligned configurations. To examine potential rotor mass reduction, the pre‐alignment concept was investigated a two‐bladed configuration by keeping the structural and aerodynamic characteristics of each blade fixed (to avoids a complete blade re‐design). Simulations for a 13.2 MW rated rotor at steady‐state conditions show that this concept‐level two‐bladed design may yield 25% rotor mass savings while also reducing average blade stress over all wind speeds. These results employed a pre‐alignment on the basis of a wind speed of 1.25 times the rated wind speed. The downwind pre‐aligned concept may also reduce damage equivalent loads on the blades by 60% for steady rated wind conditions. Even higher mass and damage equivalent load savings (relative to conventional upwind designs) may be possible for larger systems (15–20 MW) for which load‐alignment angles become even larger. However, much more work is needed to determine whether this concept can be translated into a practical design that must meet a wide myriad of other criteria. Copyright © 2017 John Wiley & Sons, Ltd.